Answer :

Given: ax + by = 7 …(i)

bx + ay = 5 …(ii)

intersection point of equation (i) and (ii) is (3,1) which means point (3,1) lies on both the lines which concludes us that point (3,1) will satisfy both the equations

Therefore

3a + b = 7 …(iii)

3b + a = 5 ⇒ a = 5 – 3b …(iv)

Putting a = 5 – 3b in equation (iii)

⇒ 3 × (5 – 3b) + b = 7

⇒ 15 – 9b + b = 7

⇒ 15 – 8b = 7

⇒ 8b = 15 – 7

⇒ 8b = 8

∴ b = 1

Put b = 1 in equation (iv)

⇒ a = 5 – (3 × 1)

⇒ a = 5 – 3

∴ a = 2

Therefore a = 2 and b = 1

Rate this question :

Attempt of the foMaharashtra Board - Algebra Papers

<span lang="EN-USMaharashtra Board - Algebra Papers

Attempt any two sMaharashtra Board - Algebra Papers

<span lang="EN-USMaharashtra Board - Algebra Papers

<span lang="EN-USMaharashtra Board - Algebra Papers

<span lang="EN-USMaharashtra Board - Algebra Papers

Attempt any threeMaharashtra Board - Algebra Papers

Attempt any threeMaharashtra Board - Algebra Papers

<span lang="EN-USMaharashtra Board - Algebra Papers

<span lang="EN-USMaharashtra Board - Algebra Papers